EMPLOYEE PERFORMANCE REVIEWED FROM REMUNERATION, EMPLOYEE MUTATION, ORGANIZATIONAL COMMITMENT, AND WORK FROM HOME POLICY IN THE REGIONAL OFFICE OF DIRECTORATE GENERAL OF TAX OF CENTRAL JAVA II IN SURAKARTA - Rahmat Fachri Safarudin; Istiatin Istiatin; Ida Aryati DPW (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2021)
This study aims to measure the influence of remuneration, employee mutation, organizational commitment, and work from home policy on employee performance both simultaneously and partially in the Regional Office of Directorate General of Tax of Central Java II. This study used quantitative descriptive method with random sampling technique. Primary data collected through the dissemination of questionnaires. Data analysis techniques using multiple linear regressions. The results indicates that (1) There is an effect of remuneration, employee mutation, organizational commitment, and work from home policy simultaneously with the performance of employees. (2) There is an influence of remuneration on the performance of employees. (3) There is an influence of employee mutation on the performance of employees. (4) There is an influence of organizational commitment to the performance of employees and (5) There is an influence of work from home policy on the performance of employees. The calculation result obtained the value of coefficient of determination of 0.868. It means that of remuneration, employee mutation, organizational commitment, and work from home policy variables have an influence of 86.8% on performance and the remaining 13.2% is influenced by other variables outside the variables studied